TRIK MAGASING: MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SD - Mahmud Syuqron; Pardimin; Muhammad Irfan (Tuladha : Jurnal Pendidikan Dasar, 2023)
Mathematics learning outcomes are still said to be low, because many students have not yet reached the KKM. Many factors can influence student learning outcomes in mathematics such as student interest in learning, learning motivation, and student learning creativity. The aim of this research is to determine the effect of applying the magazine trick in mathematics to improve student learning achievement. The population of this study consisted of 8 students who were class VI students from elementary schools in Gunungkidul. With a quantitative approach, Pre-Experimental Design type of experiment. Research results show that the magazine trick can influence students' learning interest, learning motivation and learning creativity, which supports an increase in achievement or learning outcomes. There was an increase in the average value of 28.75, from 28.75 to 86.25.